2006
DOI: 10.1111/j.1525-139x.2006.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

CRITICAL CARE ISSUES FOR THE NEPHROLOGIST: Current Diagnosis and Management of Hypertensive Emergency

Abstract: The appropriate and timely evaluation and treatment of patients with severely elevated blood pressure is essential to avoid serious adverse outcomes. Most importantly, the distinction between a hypertensive emergency (crisis) and urgency needs to be made. A sudden elevation in systolic (SBP) and/or diastolic blood pressure (DBP) that is associated with acute end organ damage (cardiovascular, cerebrovascular, or renal) is defined as a hypertensive crisis or emergency. In contrast, acute elevation in SBP and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 154 publications
(177 reference statements)
0
22
0
1
Order By: Relevance
“…Because of its rapid onset, it is suggested that in most cases an initial trigger plus the higher blood pressure activates a positive feedback loop, which stimulates the release of vasoactive mediators (Haas and Marik, 2006;Kitiyakara and Guzman, 1998). Activation of this feedback loop begins a vicious cycle, which leads to continuous organ damage and continuous increases in blood pressure (Haas and Marik, 2006;Kitiyakara and Guzman, 1998). There are many factors, which contribute to the pathophysiology of hypertensive emergency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its rapid onset, it is suggested that in most cases an initial trigger plus the higher blood pressure activates a positive feedback loop, which stimulates the release of vasoactive mediators (Haas and Marik, 2006;Kitiyakara and Guzman, 1998). Activation of this feedback loop begins a vicious cycle, which leads to continuous organ damage and continuous increases in blood pressure (Haas and Marik, 2006;Kitiyakara and Guzman, 1998). There are many factors, which contribute to the pathophysiology of hypertensive emergency.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Ang II can stimulate the release of other vasoactive and hypertensive compounds such as vasopressin, aldosterone, and catecholamines as well as stimulate the production of proinflammatory cytokines. The latter can themselves mediate opening of the BBB (Haas and Marik, 2006;Kitiyakara and Guzman, 1998;Zhang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The myocardium is the most commonly affected target organ, but encephalopathy, cerebrovascular accidents, acute papilledema, aortic dissection, renal failure, and acute pulmonary edema are frequently associated with severe BP elevation. 3 Predisposing factors for development of a hypertensive crisis include mechanical stress and injury, endothelial damage, renin-angiotensin system activation, and oxidative stress. 3 The predominant insult seems to be a cascade of humoral vasoconstrictors that leads to increased vascular resistance, generating stress and damaging the endothelium, which activates the coagulation cascade and promotes the deposition of fibrin.…”
Section: Introductionmentioning
confidence: 99%
“…3 Predisposing factors for development of a hypertensive crisis include mechanical stress and injury, endothelial damage, renin-angiotensin system activation, and oxidative stress. 3 The predominant insult seems to be a cascade of humoral vasoconstrictors that leads to increased vascular resistance, generating stress and damaging the endothelium, which activates the coagulation cascade and promotes the deposition of fibrin. These processes result in ischemia, oxidative injury, and further release of vasoactive substances that perpetuate the destructive cycle, culminating in the multiple organ dysfunction that characterizes a hypertensive emergency.…”
Section: Introductionmentioning
confidence: 99%